The Impact of Leadership Style on Teachers' Performance at SMP Al-Ikhlas Lombok - Fan, Yang; Nuruly, Santi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the impact of the principal's leadership style on teachers' performance at SMP Al-Ikhlas Al-Islami Lombok using a mixed-method approach. Data were collected through interviews and questionnaires, with findings showing that the principal adopted a democratic leadership style, involving teachers in decision-making processes. However, statistical analysis revealed that the leadership style had no significant effect on teachers' performance, with only 1.3% of performance influenced by this variable (t-count = 0.631 < t-table = 2.03951, significance = 0.599 > 0.05). Despite this, interview results highlighted that encouraging teachers to work efficiently and effectively positively influenced their performance.